Designing Stimuli‐Responsive Upconversion Nanoparticles that Exploit the Tumor Microenvironment. Issue 22 (29th March 2020) - Ovais, Muhammad; Mukherjee, Sudip; Pramanik, Arindam; Das, Devlina; Mukherjee, Anubhab; Raza, Abida; Chen, Chunying
Abstract: Tailoring personalized cancer nanomedicines demands detailed understanding of the tumor microenvironment. In recent years, smart upconversion nanoparticles with the ability to exploit the unique characteristics of the tumor microenvironment for precise targeting have been designed. To activate upconversion nanoparticles, various bio‐physicochemical characteristics of the tumor microenvironment, namely, acidic pH, redox reactants, and hypoxia, are exploited. Stimuli‐responsive upconversion nanoparticles also utilize the excessive presence of adenosine triphosphate (ATP), riboflavin, and Zn 2+ in tumors. An overview of the design of stimulus‐responsive upconversion nanoparticles that precisely target and respond to tumors via targeting the tumor microenvironment and intracellular signals is provided. Detailed understanding of the tumor microenvironment and the personalized design of upconversion nanoparticles will result in more effective clinical translation. Abstract : An overview of the design of stimuli‐responsive upconversion nanoparticles that can precisely target and respond to tumors via targeting the tumor microenvironment and intracellular signals is presented. Personalized design of upconversion nanoparticles and detailed understanding of the tumor microenvironment will result in more effective clinical translation.